A Study of the Growth and Development of Some Forestry Species under the Effect of Different Agricultural Substrates - رضوان أسامة (Latakia University Journal -Biological Sciences Series, 2021)
The study aimed to find out the effect of some agricultural substrates on the growth of seedlings of some forestry species (Pinus pinea, P. brutia, Biota orientalis, Ceratonia siliqua L.) to obtain exceled seedlings in its shoot and root system. Three agricultural substrates were used: a. Altorf (T): b. Nursery soil (S): c. mixture of Altorf and Nursery soil (TS) by (1:1). And studied several quantities indicators of growth and development of the total shoot and root system of the seedlings. Regarding the final germination, Altorf achieved the highest germination rate for species outperforming a high significant superiority for the control compared to achieving significant differences with the mixture substrate. The results indicated the continued superiority of the Altorf and significantly over the control, from germination through the length of the vegetative and root groups to the average dry weight of these groups and both plants. Consequently, Altorf plays a clear role in improving the data and indicators measured at the control alone compared to its mixture at the level of physical, chemical and biological characteristics to confirm our results on the necessity of adding Altorf to the Nursery soil to improve the germination and growth of seedlings up to the end of the success of forest afforestation projects.